Selection of Absorption Site of Ropinirole Hydrochloride in the Gastrointestinal Tract Based on its Solubility in Different Physiological Media - Kar, Koyel (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: This research work is an attempt to select a suitable absorption site in the gastrointestinal tract for ropinirole hydrochloride for its maximum therapeutic efficacy and stability and for the development of a suitable modified dosage form. Settings and Design: Ropinirole hydrochloride is commercially available as conventional tablets for oral administration, but its absorption rate varies from stomach to intestine due to the different surface area, blood flow rate, and pH. It was attempted to select a suitable absorption site in the gastrointestinal tract for ropinirole hydrochloride for its maximum therapeutic efficacy and stability and for the development of a suitable modified dosage form. In these work, three different physiological media such as saliva, gastric fluid, and intestinal fluid were chosen for solubility study. Materials and Methods: Ropinirole hydrochloride tablets, sodium hydroxide, potassium dihydrogen phosphate, salivary fluid, gastric fluid, and intestinal fluid were the important materials and Shimadzu ultraviolet (UV)-visible spectrophotometer 1601 and shaker incubator were the equipment used for the determination of absorption site. Statistical Analysis Used: UV spectrophotometric method was used for the determination of its solubility in various physiological media. Results and Discussion: From solubility studies, it was found that ropinirole hydrochloride showed the highest solubility in intestinal fluid. Solubility studies were performed in triplicate. Conclusion: Ropinirole hydrochloride showed the highest solubility in intestine. Hence, the formulation would be modified in such a way so that the drug is absorbed in the intestine.